A New Black Fly Species of Simulium (Gomphostilbia) (Diptera: Simuliidae) From Thailand - Hiroyuki Takaoka (2018)
© The Authors 2017. Published by Oxford University Press on behalf of Entomological Society of America. All rights reserved. For Permissions, please email: journals.permissions@oup.com. Simulium (Gomphostilbia) fukudae sp. nov. is described based on females, males, pupae, and larvae from Thailand. This new species is placed in the Simulium batoense species-group of Simulium (Gomphostilbia). It is characterized by the female frons almost bare, male paramere covered with minute setae, pupal gill composed of six slender filaments, pupal terminal hooks cone-shaped, and cocoon with an anterodorsal projection. Taxonomic notes are given to separate this new species from the most similar species, Simulium (G.) sextuplum Takaoka & Davies and Simulium (G.) paukatense Takaoka, both from Malaysia.